Design process for a technological support model in the communicative mediations of a virtual program in Colombia (2021)
This article, product of a research at the master's level at EAN University (2020) entitled: Design of technological model as a plan for the implementation of an optimal digital communication for the virtual program of Cidba at the University of Quindío, Colombia; developed by the authors, at the University mentioned above in 2019 and focused on: what type of technological application was relevant to maintain a fluid communication between students and teachers, since this is a continuous problem among the actors mentioned and factor of student desertion. For the investigation and collection of data, the qualitative-quantitative approach of research was used, through the implementation of a survey instrument. The results allowed to outline the design for a new virtual communication tool, supported under the Moodle platform, since this is the one that is used for teaching learning processes in the program object of study.